2016
DOI: 10.1364/oe.24.023784
|View full text |Cite
|
Sign up to set email alerts
|

Design of compact and efficient polarization-insensitive taper coupler for SiGe photonic integration

Abstract: We have proposed a polarization-insensitive laterally tapered coupler for the integration of the active Ge/SiGe multi-quantum-well device with a passive SiGe waveguide. A 45-μm-long taper is designed to achieve more than 90% coupling efficiency for both TE- and TM-polarized modes. The mode interference is utilized to obtain a compact taper coupler with high coupling efficiency. Fabrication tolerances are analyzed in terms of taper width, thickness, material refractive and operation wavelength. The results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…On the other side, compact isolation design is excluded to maintain the biaxial tensile strain of the suspended microbridge structure, resulting in parasitic capacitance. To increase the operating speed of the suspended microbridge device, the modulator structure, such as the taper waveguide coupler, active waveguide length, should be adapted to achieve a compact design and better isolation [34].…”
Section: High Frequency Responsementioning
confidence: 99%
“…On the other side, compact isolation design is excluded to maintain the biaxial tensile strain of the suspended microbridge structure, resulting in parasitic capacitance. To increase the operating speed of the suspended microbridge device, the modulator structure, such as the taper waveguide coupler, active waveguide length, should be adapted to achieve a compact design and better isolation [34].…”
Section: High Frequency Responsementioning
confidence: 99%
“…An ER of 3-4 dB was simultaneously obtained with 2-3 dB IL over 20 nm spectral ranges from 1430 to 1450 nm using a bias voltage swing between 0 and 3 V. Additionally, a low-voltage operation at 1 V and 2 V was also demonstrated. As a prospect toward reducing the taper length, in 2016, Zhou et al [69] theoretically proposed a 45-µm-long taper coupler that can be used for polarization-insensitive optical coupling between a SiGe waveguide and Ge/SiGe MQWs. Regarding evanescent integration with the SOI waveguide, Zang et al [70] recently reported in 2017 the development of an adiabatic 3D taper to assist the optical coupling between a SOI waveguide and Ge/SiGe MQW optical modulator.…”
Section: Ge/sige Quantum Well Optical Modulatorsmentioning
confidence: 99%
“…Therefore, in the integrated chip, optical signal should be routed by the passive Ge-rib waveguide and access to the highmesa active waveguide, on demand. One approach is to use taper coupler [12][13][14] for efficient coupling between the GeSn active device and passive waveguides. The taper coupler is an important approach to achieve efficient vertical coupling between layers.…”
Section: Introductionmentioning
confidence: 99%